Teachers’ Perceptions and Practices of ELT Pedagogy in Nepali Secondary Schools - Bhatt, Bhakta Raj (KMC Journal, 2025)
The pedagogy of English language teaching has undergone a significant shift in recent times, reflecting the global trends favoring communicative and student-centred approaches. This qualitative research study aims to explore the perceptions and practices of English language teachers on ELT pedagogy in Nepali secondary schools. The participants of this study were purposively selected four English language teachers who teach at the secondary-level in public schools in Kanchanpur district, Nepal. I used interview protocols and class observation notes for the collection of data and the data were analyzed through thematic analysis. The findings of the study showed that secondary-level English language teachers have been shifting their pedagogical practices from traditional teacher-centred approaches to modern innovative approaches. The study also revealed that English teachers employ mixed way of pedagogy of methods and techniques, and translanguaging as a medium of instruction in the classroom. The implication of the study is that English language teachers need to focus on student-centred pedagogical approaches in their real teaching practices. They have to create more English-learning activities in the classroom to keep the students motivated and engaged in learning so that they get more learning and practising opportunities.